Deodorization of Latex Waste and Decolorization of Textile-Coloring Agent by Omphalina sp. using Batch and Continuous Methods - Erna Puspasari; I Made Artika; Tri Panji (Current Biochemistry, 2016)
Generally industrial waste water is a pollutant to environment as it produces strong odor and color. Omphalina sp is one of white rot fungi that can be used as an odor and color effluent reducer. Omphalina sp has laccase enzyme that plays role in deodorization and decolorization. The aim of this research was to determine the best method in deodorization and decolorization among batch and continous (pack bed flow, biotray, and rotary contactor) methods. The results of deodorization and decolorization showed that the rotary contactor method was better than the batch, pack bed flow and biotray methods. At dye concentration of 50 ppm, after 24 hours treatment, the absorbance value for batch, pack bed flow, biotray, and rotary contactor methods was 0.520, 0.423, 0.425, and 0.357, respectively. At dye concentration of 150 ppm, after 24 hour treatment, the absorbance value for batch, pack bed flow, biotray, and rotary contactor methods was 0.709, 0.629, 0.658, and 0.592, respectively. At dye concentration of 50 ppm, percentage of dye absorption after 24 hour treatment for batch, pack bed flow, biotray, and rotary contactor methods was 20.550%, 35.447%, 35.141% and 45.531% respectively. At dye concentration of 150 ppm, percentage of dye absorption after 24 hour treatment for batch, pack bed flow, biotray, and rotary contactor methods was 7.320%, 17.843%, 13.987%, and 22.614%. The qmaks value at dye concentration of 50 ppm after 24 hour treatment for batch, pack bed flow, biotray, and rotary contactor methods was 0.020, 0.076, 0.083, and 0.124 respectively. qmaks value at dye concentration of 150 ppm after 24 hour treatmeny for batch, pack bed flow, biotray, and rotary contactor methods was 0.009, 0.077, 0.046, and 0.100 respectively. Odor scale for batch, pack bed flow, biotray, and rotary contactor methods decreased from 5 to 2.9, 1.4, 1.6 and 1.1 respectively.